Pengaruh Pembatalan Kontrak Terhadap Hak dan Kewajiban Para Pihak Akibat Tidak Terpenuhinya Persyaratan Bahasa Resmi - Fredrik Siregar, Aristoteles Gerhard; Gunadi, Ariawan (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
This research is very important because there are many similar cases in Indonesia. An International Arbitration award is basically final and binding, so the award should be enforceable. But sometimes it is often canceled by the rules of a country which in this case is Indonesia. That is why we need to look back at how the rules regarding this matter. Because as we know that everyone has rights, and those rights need to be protected by the state, even though in this case it is a foreign party, but based on the decision issued by the SIAC court, the person has rights that must be fulfilled based on the SIAC decision. This is because companies in Indonesia often deliberately set traps when making a contract, so that when a dispute arises, and then loses. They can file a lawsuit in the Indonesian court, or if the winning party in the arbitration court wants to execute in Indonesia, they can file a nullification of the execution due to the contract violating Indonesian laws. It will have a huge influence on the image of Indonesia towards international business, so that Indonesia will be more willing to enter into a business cooperation with foreign parties if it is often done by companies in Indonesia